Manajemen Pengembangan Staf di MTs/SMPI - Mahmud Mahmud; Mohammad Ridwan (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2022)
The back and forth of education is largely determined by the implementation that is in the hands of educators and education personnel in schools. Therefore, without neglecting the importance of other factors that influence the quality of education, the elements of educators and educational personnel in schools must receive optimal management and development. The management of education personnel includes: a) employee planning, b) employee procurement, c) employee coaching and development, d) promotions and transfers, e) compensation and awards, and f) employee dismissal. In general, the management of the coaching and development process includes several steps, namely: a) performance analysis, b) needs analysis, c) compiling instructional designs, d) approving training programs, e) implementation stage, and f) evaluation and follow-up stages. Employee development methods are carried out by: a) Guidance, b) Implementing a coaching system, c) Training both modern and external, d) Formal education, e) Promotion, f) Upgrading, and g) workshops or workshops.